Foundations of sport and exercise psychology / Robert S. Weinberg, PhD, Daniel Gould, PhD. - Weinberg, Robert S. (Robert Stephen); Gould, Daniel, 1952- (Human Kinetics, 2023)
This text provides a comprehensive view of sport and exercise psychology, with the latest research on mental health of athletes, effects of COVID-19 on athletes, mindfulness, legalised gambling, psychological issues surrounding the 2020 Olympic Games, and drug controversies.